Influence of Price and Product Quality Analysis on Frozen Fish Purchasing Decisions - Endrawati, Titin; Karundeng, Deby R.; Cakranegara, Pandu Adi; Putri, Raudya Setya Wismoko; Nofirman, Nofirman (Sangia Research Media and Publishing, 2022)
The purpose of this study was to analyze the effect of price and product quality on the decision to purchase frozen fish products at a store that sells a variety of frozen food products. The research design used in this study uses a quantitative associative method. Based on the results of data analysis that has been carried out in the first hypothesis (H1), which states that price has a positive and significant effect on purchasing decisions, the t-count value of 15,127 is greater than the t-table value, which is 1,667, testing the second hypothesis (H2). Which states that the quality of the product has a positive and significant effect on purchasing decisions the t-count value is 24,325 greater than the t-table value, which is 1,667, which means that the price and product quality produced have a positive and significant effect on consumer purchasing decisions. While the R-square value obtained is 0.781 which states that the price and product quality variables influence consumer purchasing decisions by 78.10% and the remaining 21.90% are influenced by other variables.